VIBRATION TEST RIG MODIFICATION TO SIMULATE UNBALANCE AND MECHANICAL LOOSENES SIMULTANEOUSLY - BAMANTO (NIM : 13105068); Pembimbing : Ir. Ign. Pulung Nurprasetio, MSME., MIRZA
This final project focus is on the modification of the available vibration test rig to simulate machinery faults. The main tool in this research work is the frequency domain analysis of the measured waveform. Identification will be made based on the pattern of the frequency domain data. The topic of this final project is related to condition based maintenance (CBM). Basically, CBM is a maintenance technique in which any repair decision will be based on the result of condition monitoring. The technique allows the industry to plan their maintenance and reduce down time. The main contribution of this final project is on the modification of the existing test rig to simulate several faults simultaneously. Currently, the test rig can only simulate unbalance fault. It is planned to add with mechanical looseness, since it does not require major modification. The measurement is made using piezoresistive accelerometer. The voltage output is then converted to acceleration by cross-referencing technique. The experimental result shows that the modified test rig nicely simulates both unbalance and mechanical looseness. Based on the above, we may propose the utilization of the test rig for fault diagnostic method development research.